Structure of the integrated approach to optimization of the criteria-parameter system of economic management and management of construction projects - KOZAK, Andriy; DANILOV, Serhiy; POLISHCHUK, Oleksandr; USTYNOV, Yevhen (Ways to Improve Construction Efficiency, 2025)
Modern construction project management requires an integrated approach to the formation and optimization of economic and management processes. In the context of growing requirements for the efficiency of construction activities, minimizing costs, improving the quality and efficiency of project implementation, there is a need to use an integrated approach to managing the criterion-parametric system. This allows to ensure the adaptability of business processes, their flexibility and compliance with modern requirements for resource management and innovative transformation in the construction sector. The integrated approach involves a complex interaction between economic, technological and management factors that affect the efficiency of construction projects. In particular, the definition of key parameters that allow assessing economic sustainability, financial efficiency, risk level and resource optimization plays a decisive role in modern management of the construction sector. To achieve these goals, it is important to use modern digital technologies, including artificial intelligence, big data, automated management systems and BIM technologies. One of the key aspects of the effective implementation of an integration approach is to ensure systemic coordination between all participants in a construction project: developers, investors, contractors, state regulators and end users. The interaction of these participants ensures coordinated decision-making, risk minimization and increased economic sustainability of projects. Optimization of the criterion-parametric system allows reducing transaction costs, reducing the implementation time of construction projects, ensuring transparent planning of financial flows and improving the quality of management at all stages of the project life cycle. Thus, this work is aimed at studying the structure of the integration approach to optimizing the criterion-parametric system of economic management and management of construction projects. The use of this approach allows for the implementation of innovative management methods, ensuring a high level of efficiency of construction enterprises and increasing the competitiveness of the industry as a whole.